2016
DOI: 10.1111/1475-6773.12609
|View full text |Cite
|
Sign up to set email alerts
|

Resolving Malpractice Claims after Tort Reform: Experience in a Self‐Insured Texas Public Academic Health System

Abstract: Objective To describe the litigation experience in a state with strict tort reform of a large public university health system that has committed to transparency with patients and families in resolving medical errors. Data Sources/Study Setting Secondary data collected from The University of Texas System, which self‐insures approximately 6,000 physicians at six health campuses across the state. We obtained internal case management data for all medical malpractice claims closed during 1 year before and 6 recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…4 They also found that the reform lowered annual lawsuits by more than 50%. 37 However, this was also accompanied by increases in medical board complaints, disciplinary action, and license revocations, 38 underscoring other mechanisms for corrective justice. In the states we found to have the lowest frequency of malpractice claims, a number of different tort reform measures have been enacted, such as damage caps (Hawaii, Massachusetts, Maine, Maryland, New Jersey, Alaska); joint liability reform (Hawaii, Con- necticut, New Hampshire, New Jersey, Alaska, Arizona); collateral source reform (Rhode Island, Connecticut, Massachusetts, Maine, New Jersey, Alaska, Arizona); and limiting attorney fees (Hawaii, Connecticut, Massachusetts, New Hampshire, Maine, New Jersey, Alaska).…”
Section: Discussionmentioning
confidence: 99%
“…4 They also found that the reform lowered annual lawsuits by more than 50%. 37 However, this was also accompanied by increases in medical board complaints, disciplinary action, and license revocations, 38 underscoring other mechanisms for corrective justice. In the states we found to have the lowest frequency of malpractice claims, a number of different tort reform measures have been enacted, such as damage caps (Hawaii, Massachusetts, Maine, Maryland, New Jersey, Alaska); joint liability reform (Hawaii, Con- necticut, New Hampshire, New Jersey, Alaska, Arizona); collateral source reform (Rhode Island, Connecticut, Massachusetts, Maine, New Jersey, Alaska, Arizona); and limiting attorney fees (Hawaii, Connecticut, Massachusetts, New Hampshire, Maine, New Jersey, Alaska).…”
Section: Discussionmentioning
confidence: 99%
“…). The Texas project implemented in a state with a “low‐tort” environment—where the malpractice litigation risk for a public university was already diminished substantially (Sage, Harding, and Thomas ). The fact that challenges were encountered across the PSML portfolio of demonstration projects in no way diminishes the accomplishments of individual projects, but the failure to fully implement in nonacademic settings leaves an unanswered policy question.…”
Section: Findings From Psml Demonstration Sitesmentioning
confidence: 99%
“…Sage et al. share the results of a closed claims analysis conducted at the University of Texas System to better understand the organization's malpractice claims experience after the implementation of tort reform in Texas (Sage, Harding, and Thomas ).…”
Section: Contents Of This Special Issuementioning
confidence: 99%